2017
DOI: 10.11157/anzswj-vol29iss3id377
|View full text |Cite
|
Sign up to set email alerts
|

Making the connections: A practice model for reflective supervision

Abstract: INTRODUCTION:Over several decades, social work in Aotearoa New Zealand has undergone major alterations in service delivery in response to the management of risk and surveillance of practice within the neoliberal government agenda. Working in such an environment, social workers struggle to critically explore their position and professionally develop their practice. To support current professional practice in social work, reflective supervision has become a necessity for analysing and amplifying positive practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In England, there has also been a concerted effort in practice to provide more effective supervisory support, particularly for early-career practitioners (Schraer, 2016). Similar efforts have been made elsewhere, as Rankine (2017) outlines in relation to Aotearoa New Zealand. Despite these well-intended and in many cases successful efforts the general picture remains one of concern about the managerial capture of supervision (Manthorpe, Moriarty, Hussein, Stevens, & Sharpe, 2015;Wilkins, Forrester, & Grant, 2017).…”
Section: Original Articlementioning
confidence: 72%
See 1 more Smart Citation
“…In England, there has also been a concerted effort in practice to provide more effective supervisory support, particularly for early-career practitioners (Schraer, 2016). Similar efforts have been made elsewhere, as Rankine (2017) outlines in relation to Aotearoa New Zealand. Despite these well-intended and in many cases successful efforts the general picture remains one of concern about the managerial capture of supervision (Manthorpe, Moriarty, Hussein, Stevens, & Sharpe, 2015;Wilkins, Forrester, & Grant, 2017).…”
Section: Original Articlementioning
confidence: 72%
“…Turner-Daly and Jack (2015) found that supervision sessions in England may focus on case-management to the exclusion of much else, while Baginsky et al (2010) reported that senior managers often consider supervision to be a mechanism for performance-management, rather than a forum for support. In Aotearoa New Zealand, similar concerns have been expressed by Rankine (2017) and Moorhouse, Hay, and O'Donoghue (2014), with the suggestion that supervision functions in many cases as a mechanism for the surveillance of practice within a neoliberal context.…”
Section: Original Articlementioning
confidence: 84%
“…Within the organisation it is easier to fully manage service delivery, facilitate professional development and focus practitioner work (Beddoe & Davys, 2016). Rankine (2017) noted that internal supervision can be used to recreate and change team culture through exploring the assumptions behind staff actions and the organisation's policies and, if there are differences noted, whether they could be used to improve the client service.…”
Section: Internal Supervisionmentioning
confidence: 99%
“…Internal supervision does, however, tend to emphasise organisational policies and tends to focus on casework and organisational goals (Rankine, 2017). For this reason it can be useful to split the session between focusing on organisation requirements and using the supervision time to let the person explore possible options that would benefit clients most.…”
Section: Internal Supervisionmentioning
confidence: 99%
“…Matt Rankine (2017), in 'Making the connections: A practice model for reflective supervision,' describes a new model of reflective supervision arguing for an approach to community social work supervision that is grounded in a co-constructed partnership between the supervisor and supervisee. Rankine presents a four-layered model to support critical thinking in the diverse socio-political and cultural contexts of social work and promotes social justice strategies.…”
mentioning
confidence: 99%